Republic of Serbia : Request for Stand-by Arrangement: Staff Report; Staff Statement; Press Release; and Statement by the Executive Director for the Republic of Serbia. (IMF Staff Country Reports; Country Report ;, 2011)
Serbia's transition to a more sustainable growth model remains incomplete and fragile. A precautionary Stand-By Arrangement (SBA) has been requested to insure against external risks and to provide a policy anchor. The program represents a prudent step in the present uncertain global and regional environment. However, without improving Serbia's difficult investment climate, the economy cannot deliver sustainable growth. Executive Directors expect that a steadfast program implementation along with responsiveness to new adverse developments will lead the Serbian economy to overcome its present difficulties.